Electrode catalyst slurry and preparation method thereof, catalyst coating membrane, and fuel cell

By locking the spatial structure of the catalyst and ionic polymer and vacuum drying and crushing during secondary dispersion, a catalyst-ionic polymer solid is formed, which solves the problem of uneven distribution in the fuel cell slurry and realizes the catalyst slurry Uniformity and stability improve production efficiency.

CN114709434BActive Publication Date: 2025-02-11CHINA AUTOMOTIVE INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210417561.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-20
Publication Date
2025-02-11
Estimated Expiration
2042-04-20

AI Technical Summary

Technical Problem

There is a problem of uneven distribution of ionic polymers and catalysts in the slurry configuration of existing fuel cells, resulting in reduced catalyst utilization, increased cost, and flooding and electrochemical corrosion during the production process.

Method used

By locking the spatial structure of the catalyst and ionic polymer in advance, the stability of the catalyst slurry is ensured during secondary dispersion, and the catalyst-ionic polymer solid is formed by vacuum drying and crushing, and the second stirring and ball milling are ensured. It is evenly dispersed.

Benefits of technology

The uniformity and stability of the catalyst slurry are achieved, the problems of flooding and electrochemical corrosion are avoided, the utilization rate and production efficiency of the catalyst are improved, and it is suitable for large-volume mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114709434B_ABST
    Figure CN114709434B_ABST
Patent Text Reader

Abstract

The present invention provides an electrode catalyst slurry and a preparation method thereof, a catalyst coating membrane, and a fuel cell, wherein the preparation method comprises the following steps: (1) mixing a solution of a catalyst and an ionic polymer and subjecting the mixture to a first stirring to obtain a mixed material; (2) subjecting the mixed material to vacuum drying to obtain a catalyst-ionic polymer solid body; (3) subjecting the catalyst-ionic polymer solid body to pulverization, mixing the pulverized material, an organic solvent, and water, and subjecting the mixture to a second stirring and ball milling in sequence to obtain an electrode catalyst slurry. The present invention is prepared by changing the preparation of a catalyst slurry from one step to two steps of the catalyst slurry, and adopting a vacuum drying method to prepare the catalyst-ionic polymer solid body, thereby locking the spatial structure of the catalyst and the ionic polymer, and ensuring the stability of the catalyst slurry during the secondary dispersion, and can be suitable for the preparation of catalyst slurry for large-volume mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to an electrode catalyst slurry and a preparation method thereof, a catalyst coating membrane, and a fuel cell. Background Art

[0002] Fuel cells can convert chemical energy in fuel into electrical energy, and proton exchange membrane fuel cells have the advantages of low operating temperature and high power density.

[0003] However, the existing fuel cell slurry configuration process will cause the problem of uneven distribution of ion polymers and catalysts. The larger the volume of slurry configured during the production process, the more serious the uneven problem. In the part with too much ion polymer, it provides supersaturated reactants hydrogen protons and water but insufficient catalyst, which is prone to problems such as water flooding and electrochemical corrosion of carbon carriers; in the part with too little ion polymer, the catalyst is oversaturated, the catalyst utilization rate is reduced, and the cost is increased.

[0004] There have been some preliminary studies on the problem of uneven slurry configuration. For example, CN114050277A discloses a method for preparing catalyst slurry for fuel cells. However, this method still cannot achieve uniform preparation during mass production and large-volume manufacturing.

[0005] CN113921831A discloses an electrode catalyst slurry and a preparation method thereof, wherein the specific method used includes: first mixing and dispersing the catalyst with an ionic polymer solution, standing and self-assembling at 90°C to 110°C, filtering and collecting the solid, and freeze-drying to obtain an ionic polymer-coated catalyst; second mixing and dispersing the ionic polymer-coated catalyst and a solvent to obtain an electrode catalyst slurry. By first mixing and dispersing the catalyst with an ionic polymer solution, and controlling the standing and self-assembling under certain conditions, and freeze-drying, the surface of the catalyst is coated with an ionic polymer film with uniform pores, which effectively solves the problem of uneven distribution of the ionic polymer and the catalyst when the catalyst, ionic polymer and solvent are added together in the traditional method, but many steps involved in this method are difficult to mass produce, and are prone to deviations in the ratio of the catalyst and the ionic polymer, and the stability of mass production is difficult to control.

[0006] CN111135761A discloses a method for preparing a fuel cell catalyst slurry that resists sedimentation, comprising the following steps: (1) mixing a perfluorosulfonic acid solution, isopropanol and water, and performing magnetic stirring after sealing to form a dispersed solution; (2) mixing the catalyst with the dispersed solution, and ultrasonically dispersing the mixture to obtain a preliminary dispersed catalyst slurry; (3) using a stator-rotor stirrer to further perform high shear dispersion on the obtained preliminary dispersed catalyst slurry to obtain a secondary dispersed catalyst slurry; (4) then using a homogenizer to homogenize and disperse the secondary dispersed catalyst slurry under vacuum conditions to obtain a stable catalyst slurry, and the process is completed. However, the catalyst slurry is only suitable for small-batch manufacturing, and it is difficult to achieve consistency and homogenization in mass production.

[0007] Therefore, it is necessary to develop a method that can be suitable for large-volume mass production slurry preparation to improve the uniformity and consistency of the catalyst slurry preparation process. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides an electrode catalyst slurry and a preparation method thereof, a catalyst coating membrane, and a fuel cell. By locking the spatial structure of the catalyst and the ion polymer in advance, the stability of the catalyst slurry is ensured during the secondary dispersion, thereby solving the problem in the prior art that it is difficult to ensure uniformity and stability of large-volume mass production of catalyst slurry.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing an electrode catalyst slurry, the preparation method comprising the following steps:

[0011] (1) mixing a solution of a catalyst and an ion polymer and stirring the mixture to obtain a mixed material;

[0012] (2) the mixed material is vacuum dried to obtain a catalyst-ion polymer solid body;

[0013] (3) The catalyst-ion polymer solid body is crushed, and the crushed material, organic solvent and water are mixed, and then subjected to a second stirring and ball milling in sequence to obtain an electrode catalyst slurry.

[0014] The preparation method provided by the present invention is simple and easy to operate, and is suitable for industrial mass production. In addition, the ratio between the catalyst and the ionic polymer can be guaranteed during the mass production process. In the first stirring process, only the ionic polymer solution and the catalyst are added, and no additional water is added (only the water solvent that may be brought by the purchased ionic polymer solution), so that it is more conducive to the combination of the ionic polymer and the catalyst; and through the vacuum drying step, the rapid evaporation of the liquid phase in the mixed material is achieved, the spatial structure of the ionic polymer and the catalyst is locked, and a catalyst-ionic polymer solid body is formed. Since there is no need to adopt filtering, washing and other steps, it can be ensured that the mass ratio of the originally added catalyst and the ionic polymer is completely retained in the catalyst-ionic polymer solid body, so that the ratio stability of the two can be guaranteed during the mass production process; the catalyst-ionic polymer solid body is crushed and then dispersed in an organic solvent and water, and a second stirring and ball milling are performed. At this time, it is sufficient to ensure that the crushed material is evenly dispersed in the solution, and the catalyst and the ionic polymer are evenly distributed due to the solid body formed in the early stage, thereby solving the problem that it is difficult to ensure uniformity and stability of large-volume mass production catalyst slurry.

[0015] In the present invention, the catalyst and the ionic polymer are dispersed by the first stirring method, which is a direct intervention, has high reliability and safety, is suitable for water-soluble and organic-soluble ionic polymers, provides a higher adaptability range, and is suitable for research and development and mass production.

[0016] The catalyst-ion polymer solid complex obtained by the present invention is an integral solid phase, similar to the integral solid phase of a "tea cake", and is not a single dispersed solid particle.

[0017] Preferably, the mixing in step (1) comprises: firstly adding a catalyst into a container, then introducing argon gas to expel the air, and then adding the ion polymer solution.

[0018] The present invention preferably adopts the above-mentioned method of adding materials, which can further avoid the combustion of the catalyst and the ion polymer in the air environment, and has a higher safety advantage.

[0019] Preferably, the catalyst in step (1) comprises platinum alloy carbon and / or platinum carbon.

[0020] Preferably, the particle size of the catalyst is 1 to 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0021] Preferably, the ionic polymer comprises perfluorosulfonic acid resin.

[0022] The present invention has no special limitation on the perfluorosulfonic acid resin. Any perfluorosulfonic acid resin that can be used for the preparation of electrode catalyst slurry and is well known to those skilled in the art can be used. It can also be adjusted according to actual conditions. For example, it can be a commercially available perfluorosulfonic acid resin such as Chemours, Dongyue, Solvay, 3M or AGC, for example, it can be any one of Chemours-D2020, Chemours-D2021, Dongyue-EW910, 3M-EW725, 3M-EW795, 3M-EW980, Solvay-EW729, Solvay-EW790, AGC-IC100 or AGC-IC154, or a combination of at least two of them.

[0023] Preferably, the solid content of the ionic polymer solution is 5% to 30%, for example, 5%, 8%, 10%, 12%, 13%, 14%, 15%, 18%, 20%, 22%, 23%, 25%, 28% or 30%, etc. The concentration of the general solution is 10% to 30%, and within this concentration range, the effect on the first stirring is not great.

[0024] Preferably, the solvent in the ionic polymer solution is the solvent of the ionic polymer solution when purchased. The solvent includes but is not limited to water and / or an organic solvent, but no additional water is added during the mixing in step (1).

[0025] Preferably, the organic solvent in the solution of the ionic polymer comprises an alcohol.

[0026] The alcohol in the solution of the ionic polymer of the present invention can be, for example, any one of a monohydric alcohol, a dihydric alcohol or a trihydric alcohol, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of a monohydric alcohol and a dihydric alcohol, a combination of a dihydric alcohol and a trihydric alcohol, a combination of a trihydric alcohol and a monohydric alcohol, etc.

[0027] Preferably, the mass ratio of the ionomer to the carbon in the catalyst is 0.6 to 1.5:1, for example, it can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 0.8 to 1.2:1.

[0028] Preferably, the catalyst in step (1) is pretreated before mixing.

[0029] Preferably, the pretreatment includes drying the catalyst.

[0030] Preferably, the drying temperature is 55-70°C, for example, it can be 55°C, 57°C, 59°C, 60°C, 62°C, 64°C, 65°C, 67°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0031] Preferably, the drying time is 20 to 24 hours, for example, 20 hours, 20.5 hours, 20.9 hours, 21.4 hours, 21.8 hours, 22.3 hours, 22.7 hours, 23.2 hours, 23.6 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0032] Preferably, the drying process comprises a vacuum drying process.

[0033] Preferably, the first stirring in step (1) comprises ultrasonic oscillation stirring and high-speed stirring performed sequentially.

[0034] Preferably, the ultrasonic stirring time is 10 to 25 min, for example, it can be 10 min, 12 min, 14 min, 15 min, 17 min, 19 min, 20 min, 22 min, 24 min or 25 min, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0035] Preferably, the frequency of the ultrasonic oscillation stirring is 20-30HKz, for example, it can be 20HKz, 21HKz, 22HKz, 23HKz, 24HKz, 25HKz, 26HKz, 27HKz, 28HKz or 30HKz.

[0036] Preferably, the stirring speed of the high-speed stirring is 10000-30000 r / min, for example, it can be 10000 r / min, 12000 r / min, 14000 r / min, 16000 r / min, 18000 r / min, 21000 r / min, 23000 r / min, 25000 r / min, 27000 r / min or 30000 r / min, but is not limited to the listed values, and other values ​​not listed in this range are also applicable.

[0037] In the present invention, it is preferred that the speed of the first stirring is within the above range, so that the catalyst and the ionic polymer can collide and combine with each other, and the combination is more uniform.

[0038] Preferably, the temperature of the high-speed stirring is 10-25°C, for example, it can be 10°C, 12°C, 13°C, 14°C, 15°C, 16°C, 18°C, 20°C, 21°C, 22°C or 25°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0039] Preferably, the high-speed stirring time is 20 to 40 min, for example, it can be 20 min, 22 min, 23 min, 24 min, 25 min, 28 min, 30 min, 32 min, 35 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the vacuum drying in step (2) is carried out in a vacuum drying oven.

[0041] Preferably, the evacuated gas is drawn out from the vacuum drying oven, condensed, and then passed through a vacuum pump.

[0042] The most critical step of the present invention is to form a catalyst-ion polymer solid complex by vacuum drying. In this step, the solvent in the ion polymer solution needs to be volatilized quickly and in large quantities. The organic solvent has a certain damaging effect on the pump. Long-term industrial production will shorten the service life of the vacuum pump. Therefore, the vacuumed gas is first condensed to remove part of the solvent and then passed through the vacuum pump, which significantly extends the service life of the vacuum pump.

[0043] Preferably, the absolute vacuum degree of the vacuum drying is less than 133 Pa, for example, it may be 132 Pa, 130 Pa, 120 Pa, 110 Pa, 100 Pa, 90 Pa or 80 Pa, etc.

[0044] Preferably, the vacuum drying temperature is 55-65°C, for example, it can be 55°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0045] The present invention further prefers that the temperature of vacuum drying is within the above range, which can achieve rapid volatilization of the solvent in the ionic polymer solution at a relatively low temperature, thereby solidifying the catalyst and the ionic polymer together in a short time, which is more conducive to the formation of a spatial structure in the catalyst-ionic polymer solid body.

[0046] Preferably, the vacuum drying time is 20 to 40 min, for example, it can be 20 min, 22 min, 23 min, 24 min, 25 min, 28 min, 30 min, 32 min, 34 min, 35 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0047] Preferably, the comminution in step (3) includes grinding.

[0048] Preferably, the particle size of the crushed material is 8 to 15 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0049] The present invention preferably controls the particle size of the pulverized material within the above range, which is more conducive to subsequent dispersion and improves the uniformity of the final catalyst slurry.

[0050] Preferably, the stirring speed of the second stirring in step (3) is 10000-20000 r / min, for example, it can be 10000 r / min, 11000 r / min, 12000 r / min, 13000 r / min, 14000 r / min, 15000 r / min, 16000 r / min, 17000 r / min, 18000 r / min or 20000 r / min, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0051] In the present invention, the second stirring improves the dispersion uniformity of the solid phase in the liquid phase by means of high-speed shear stirring.

[0052] Preferably, the second stirring time is 5 to 15 min, for example, it can be 5 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0053] Preferably, the particle size of the material after ball milling in step (3) is 1 to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0054] Preferably, the abrasive ratio of the ball mill is 0.8 to 1.2:1, for example, it can be 0.8:1, 0.82:1, 0.85:1, 0.9:1, 0.95:1, 1.0:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0055] Preferably, the ball milling time is 30 to 60 min, for example, 30 min, 32 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0056] Preferably, the rotation speed of the ball mill is 100-800 rpm, for example, it can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0057] Preferably, the organic solvent in step (3) comprises alcohol.

[0058] The alcohol described in step (3) of the present invention can be, for example, any one of a monohydric alcohol, a dihydric alcohol or a trihydric alcohol, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of a monohydric alcohol and a dihydric alcohol, a combination of a dihydric alcohol and a trihydric alcohol, a combination of a trihydric alcohol and a monohydric alcohol, etc.

[0059] The present invention has no special limitation on the ratio of water, organic solvent and crushed material in step (3), and the ratio of electrode catalyst slurry commonly used by those skilled in the art can be adopted. For example, the solid content in the catalyst slurry is in the range of 5 to 30%, for example, it can be 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 18%, 20%, 22%, 25%, 28% or 30%, etc.; the mass ratio of perfluorosulfonic acid resin to carbon carrier in the catalyst in the solid content I / C=0.6 to 1.5:1, for example, it can be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, etc.

[0060] The preparation method of the electrode catalyst slurry described in the present invention can be applied to the preparation of catalyst slurries of different scales, and is particularly suitable for the preparation of large-volume catalyst slurries for mass production, wherein more than 50L of electrode catalyst slurry can be produced at a time, and the ratio of the catalyst and the ionic polymer in each part of the slurry can still be ensured to be uniform, and the power density of the overall slurry after coating is stable.

[0061] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0062] (1) First, a catalyst (average particle size of 1 to 10 μm) is added to a container, and then argon gas is introduced to expel air, and then an ion polymer solution (solid content of 5% to 30%) is added, the mass ratio of the ion polymer to the carbon in the catalyst is 0.6 to 1.5:1, and ultrasonic oscillation stirring at a frequency of 20 to 30 HKz for 10 to 25 minutes and high-speed stirring at 10,000 to 30,000 r / min for 20 to 40 minutes is performed in sequence to obtain a mixed material;

[0063] (2) the mixed material is vacuum dried at 55-65° C. and less than 133 Pa for 20-40 min, and the evacuated gas is extracted from the vacuum drying oven, condensed, and then passed through a vacuum pump to obtain a catalyst-ion polymer solid body;

[0064] (3) The catalyst-ion polymer solid body is ground and pulverized, and the pulverized material with an average particle size of 8 to 15 μm, an organic solvent and water are mixed, and the mixture is sheared and stirred at 10,000 to 20,000 r / min for 5 to 15 min and ball milled in sequence. The grinding ratio of the ball mill is (0.8 to 1.2):1, the time is 30 to 60 min, and the rotation speed is 100 to 800 rpm to obtain an electrode catalyst slurry containing 1 to 10 μm solids.

[0065] In a second aspect, the present invention provides an electrode catalyst slurry, wherein the electrode catalyst slurry is prepared according to the preparation method of the electrode catalyst slurry in the first aspect.

[0066] The electrode catalyst slurry provided in the second aspect of the present invention is prepared by the preparation method of the first aspect and has high uniformity. Therefore, it is not easy to cause problems such as water flooding and electrochemical corrosion of carbon carriers during use, and the catalyst utilization rate is reduced, thereby reducing costs.

[0067] In a third aspect, the present invention provides a catalyst coated membrane comprising a cathode catalyst layer, an anode catalyst layer and a proton exchange membrane, wherein the anode catalyst layer and the cathode catalyst layer are arranged on both sides of the proton exchange membrane, and the anode catalyst layer and / or the anode catalyst layer are made of the electrode catalyst slurry as described in the second aspect.

[0068] The catalyst coating membrane provided by the invention has uniform components and excellent performance.

[0069] In a fourth aspect, the present invention provides a fuel cell, comprising the catalyst coating membrane described in the third aspect.

[0070] The fuel cell provided by the fourth aspect of the present invention has stable performance and long service life.

[0071] The present invention has no special restrictions on other components and structures in the above-mentioned fuel cell. Any components and structures of fuel cells well known to those skilled in the art may be adopted, and may also be adjusted according to actual processes.

[0072] Compared with the prior art, the present invention has at least the following beneficial effects:

[0073] (1) The electrode catalyst slurry provided by the present invention has uniform components, is basically free of problems such as water flooding and electrochemical corrosion of carbon carriers, and has a high catalyst utilization rate;

[0074] (2) The preparation method of the electrode catalyst slurry provided by the present invention can produce a catalyst slurry with stable and consistent performance. Under the preferred conditions, it can ensure that the particle size increases from 1 to 5 μm to 1 to 15 μm only after standing for 2 hours, and the particle size increases from 1 to 5 μm to 1 to 20 μm only after standing for 4 hours. In addition, the slurry is evenly proportioned at all places, and 10 pieces of 50 cm are arranged into a single cell. 2 The average power density of MEA in the active area (@0.65V) is above 1.02, with a standard deviation within 0.008, and is suitable for industrial mass production and the preparation of catalyst slurries of more than 50L, solving the problem of large-volume catalyst slurries being difficult to even out during production.

[0075] (3) The fuel cell provided by the present invention has stable performance, long service life and high safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 It is a schematic diagram of a vacuum condensation device provided in a specific embodiment of the present invention.

[0077] In the figure: 1-gas inlet; 2-gas outlet; 3-condensation device; 4-cooling jacket; 5-cooling medium; 6-organic condensate. DETAILED DESCRIPTION

[0078] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0079] For the convenience of experimental comparison, the following examples and comparative examples adopt the following pretreatment: the catalyst is dried in a vacuum drying oven at 60°C for 20 hours to facilitate more accurate weighing; the container is vibrated in an ultrasonic cleaner for 30 minutes and then rinsed with deionized water, then placed in an oven at 85°C for 1 hour and cooled to room temperature before being taken out for use. The present invention can also be carried out using other experimental pretreatment parameters.

[0080] In order to improve the service life of the vacuuming device, the schematic diagram of the vacuuming condensing device 3 provided in this specific embodiment is as follows: Figure 1 As shown, from Figure 1 It can be seen that the present invention adds a condensing device 3 between the vacuum drying box and the vacuum pump. The condensing device 3 is provided with a gas inlet 1, a gas outlet 2 and a cooling jacket 4. The gas inlet 1 is connected to the vacuum drying box, and the gas inlet 1 is deeper into the condensing device 3 than the gas outlet 2; the gas outlet 2 is connected to the vacuum pump; and the cooling jacket 4 is provided with a cooling medium 5.

[0081] The present invention has no special limitation on the cooling medium 5 , and any cooling medium known to those skilled in the art may be used, such as liquid nitrogen.

[0082] Figure 1 During the operation of the condensing device 3 shown, the inner bottom of the condensing device 3 will contain cooled organic condensate 6, thereby greatly alleviating the influence of the organic solvent on the life of the vacuum pump.

[0083] Example 1

[0084] This embodiment provides a method for preparing an electrode catalyst slurry, the preparation method comprising the following steps:

[0085] (1) First, a catalyst (platinum alloy catalyst platinum cobalt carbon with an average particle size of 8 μm, a platinum content of 50 w% and a cobalt content of 5.0 w%) is added to a container, and then argon gas is introduced to exhaust the air, and then an ion polymer solution (Chemours-D2020, solid content of 20%) is added, the mass ratio of the ion polymer to the carbon in the catalyst is 0.8:1, and the mixture is subjected to ultrasonic oscillation stirring at a frequency of 26 HKz for 15 minutes, cooling at 20° C., and high-speed stirring at a controlled condition of 12000 r / min for 30 minutes at room temperature to obtain a mixed material;

[0086] (2) the mixed material is vacuum dried at 60° C. and less than 133 Pa for 30 min, and the gas after vacuuming is extracted from the vacuum drying oven, condensed, and then passed through a vacuum pump to obtain a catalyst-ion polymer solid body;

[0087] (3) The catalyst-ion polymer solid body is ground and pulverized, and the pulverized material with an average particle size of 10 μm, isopropanol and water are mixed, and the mass ratio of isopropanol to water is 1:1. The material is sheared and stirred at 15000 r / min for 10 min and ball milled in sequence. The grinding ratio of the ball mill is 0.8:1, the time is 30 min, and the rotation speed is 600 rpm, to obtain an electrode catalyst slurry containing 1-5 μm solids.

[0088] Example 2

[0089] This embodiment provides a method for preparing an electrode catalyst slurry, the preparation method comprising the following steps:

[0090] (1) First, a catalyst (platinum alloy catalyst platinum carbon with an average particle size of 5 μm and a platinum content of 50 w%) is added to a container, and then argon gas is introduced to exhaust the air and then an ion polymer solution (AGC-IC100, solid content of 26%) is added, the mass ratio of the ion polymer to the carbon in the catalyst is 0.6:1, and the mixture is subjected to ultrasonic oscillation stirring at a frequency of 30 HKz for 10 minutes, cooling at 10° C., and high-speed stirring at a controlled condition of 10,000 r / min for 30 minutes to obtain a mixed material;

[0091] (2) the mixed material is vacuum dried at 65° C. and less than 133 Pa for 30 min, and the gas after vacuuming is extracted from the vacuum drying oven, condensed, and then passed through a vacuum pump to obtain a catalyst-ion polymer solid body;

[0092] (3) The catalyst-ion polymer solid body is ground and pulverized, and the pulverized material with an average particle size of 8 μm, ethanol and water are mixed, and the mass ratio of ethanol to water is 1.2:1. The material is sheared and stirred at 20,000 r / min for 15 min and ball milled in sequence. The ball milling has an abrasive ratio of 1.2:1, a time of 45 min, and a rotation speed of 750 rpm to obtain an electrode catalyst slurry containing solids of 1 to 5 μm.

[0093] Example 3

[0094] This embodiment provides a method for preparing an electrode catalyst slurry, the preparation method comprising the following steps:

[0095] (1) First, 1000 g of a catalyst (platinum alloy catalyst platinum cobalt carbon with an average particle size of 8 μm, a platinum content of 50 w% and a cobalt content of 5.0 w%) is added to a large container, and then argon gas is introduced to exhaust the air and then an ion polymer solution (AGC-100, solid content 26%) is added, the mass ratio of the ion polymer to the carbon in the catalyst is 1.5:1, and the mixture is subjected to ultrasonic oscillation stirring at a frequency of 26 HKz for 25 min, cooling at 22° C., and high-speed stirring at a controlled condition of 30,000 r / min for 30 min to obtain a mixed material;

[0096] (2) the mixed material is vacuum dried at 55° C. and less than 133 Pa for 60 min, and the gas after vacuuming is extracted from the vacuum drying oven, condensed, and then passed through a vacuum pump to obtain a catalyst-ion polymer solid body;

[0097] (3) The catalyst-ion polymer solid body is ground and pulverized, and the pulverized material with an average particle size of 15 μm, isopropanol and water are mixed, and the mass ratio of isopropanol to water is 0.8:1. The material is sheared and stirred at 10,000 r / min for 5 min and ball milled in sequence. The grinding ratio of the ball mill is 1.2:1, the time is 60 min, and the rotation speed is 750 rpm, to obtain an electrode catalyst slurry containing 2 to 6 μm solids.

[0098] Example 4

[0099] This embodiment provides a method for preparing an electrode catalyst slurry. The preparation method is the same as that of Embodiment 1 except that the mass ratio of the ion polymer to the carbon in the catalyst in step (1) is replaced from 0.8:1 to 1:1.

[0100] Example 5

[0101] This embodiment provides a method for preparing an electrode catalyst slurry. The preparation method is the same as that of Embodiment 1 except that the mass ratio of the ion polymer to the carbon in the catalyst in step (1) is replaced from 0.8:1 to 1.2:1.

[0102] Example 6

[0103] This embodiment provides a method for preparing an electrode catalyst slurry. The preparation method is the same as that of Embodiment 1 except that the high-speed stirring in step (1) is performed at 95° C.

[0104] Example 7

[0105] This embodiment provides a method for preparing an electrode catalyst slurry. The preparation method is the same as that of Embodiment 1 except that the vacuum drying temperature in step (2) is only 30°C.

[0106] Example 8

[0107] This embodiment provides a method for preparing an electrode catalyst slurry. The preparation method is the same as that of Embodiment 1 except that the vacuum drying temperature in step (2) is 70° C.

[0108] Comparative Example 1

[0109] This comparative example provides a method for preparing an electrode catalyst slurry, which adopts the same composition and ratio as Example 1, and the specific steps are:

[0110] After adding the ionomer to 10g of the catalyst, microwave vibration was applied for 25min, and then a mixed solution of isopropanol and water (the mass ratio of isopropanol to water was 1:1) was added, and high-speed stirring was used for dispersion (temperature control at 20°C, stirring time for 30min, 30000r / min), and the slurry viscosity was adjusted to 50Pa·s.

[0111] Comparative Example 2

[0112] This comparative example provides a method for preparing an electrode catalyst slurry. In the preparation method, except that the mass ratio of the ion polymer to the carbon in the catalyst is 1:1, the rest is the same as that of comparative example 1.

[0113] Comparative Example 3

[0114] This comparative example provides a method for preparing an electrode catalyst slurry. In the preparation method, except that the mass ratio of the ion polymer to the carbon in the catalyst is 1.2:1, the rest is the same as that of comparative example 1.

[0115] Comparative Example 4

[0116] This comparative example provides a method for preparing an electrode catalyst slurry. The preparation method is the same as Example 1 except that 20 wt % of water is additionally added in step (1).

[0117] Comparative Example 5

[0118] This comparative example provides a method for preparing an electrode catalyst slurry. The preparation method is the same as Example 1 except that in step (1), the vacuum drying is not performed but the filtered solid phase is freeze-dried at -30°C for 40 hours.

[0119] Comparative Example 6

[0120] This comparative example provides a method for preparing an electrode catalyst slurry. The preparation method is the same as Example 1 except that the ball milling in step (3) is not performed.

[0121] Comparative Example 7

[0122] This comparative example provides a method for preparing an electrode catalyst slurry, and the preparation method is carried out by the method of Example 1 in CN113921831A.

[0123] Many steps in this comparative example are difficult to mass produce and easily lead to deviations in the ratio of catalyst and ion polymer, and the stability of mass production is difficult to control.

[0124] (1) Stability test

[0125] The catalyst slurries prepared in the above-mentioned embodiments and comparative examples were allowed to stand, and the particle sizes of the slurries before and after the standing were tested. The test data are shown in Table 1.

[0126] Table 1

[0127]

[0128]

[0129] (2) Uniformity test and battery performance test

[0130] The electrode catalyst slurry prepared in the embodiment and the comparative example was scraped on one side of the proton exchange membrane at room temperature using a slot extrusion coater, and then dried. The proton exchange membrane was then turned over and scraped on the other side of the proton exchange membrane at room temperature, and then dried, respectively, as the cathode and anode. The platinum loading density of the cathode coating was 0.075 mg / cm 2 The platinum loading density of the anode coating is 0.175 mg / cm 2 ; Drying was carried out under vacuum adsorption conditions, the drying temperature was 80-90°C, the drying time was 30 minutes, and 50 cm 2 CCM of the active area; frame films are placed on both sides of the prepared CCM, and hot pressing is performed at 0.6MPa, 160℃ for 2min to obtain a five-in-one; then hot melt adhesive is applied around the carbon paper, and hot pressing is performed at 0.4MPa, 140℃ for 20s to obtain a membrane electrode assembly.

[0131] Place a cathode plate on the cathode end plate with the current collector, place the membrane electrode assembly prepared by the above method in the middle according to the cathode and cathode, install the anode plate, position and align the anode end plate with the current collector, cover it, lock the battery with screws, tighten it with a torque wrench, and assemble it into a single battery.

[0132] The assembled single cell is connected to the fuel cell test platform for testing. Test conditions: cell temperature 70°C, gas excess coefficient H 2 / Air=1.5 / 2.5,humidity 70%RH,H 2 Side pressure 250kPa, Air side pressure 250kPa.

[0133] The test results of the above embodiments and comparative examples are shown in Table 2.

[0134] Table 2

[0135]

[0136]

[0137] From Table 1 and Table 2, we can see the following points:

[0138] (1) It can be seen from Examples 1 to 3 that the electrode catalyst slurry and the preparation method thereof provided by the present invention can be adapted to different types of catalysts and ion polymer combinations, and can be applied to the slurry configuration of the R&D level (catalyst 10g) and the production level (catalyst 1000g). The particle size can be increased from 1 to 5 μm to 1 to 20 μm after standing for 4 hours, and the slurry is evenly proportioned everywhere. After being configured into a single cell, 10 pieces of 50 cm 2 The average power density of MEA in the active area (@0.65V) is above 1.02, and the standard deviation is within 0.008, which solves the problem of difficulty in ensuring uniformity and stability of catalyst slurry in large-volume mass production in the prior art.

[0139] (2) It can be seen from Examples 1, 4 and 5 that the electrode catalyst slurry and the preparation method thereof provided by the present invention can be applied to the preparation of catalyst slurries with different ion polymer contents. The particle size of the electrode catalyst slurry increases from 1 to 5 μm to 1 to 20 μm after standing for 4 hours. The particle size of the catalyst slurry can be effectively controlled. The power density of the single cell varies accordingly according to the different contents of the ion polymer.

[0140] (3) Based on Examples 1 and 6, it can be seen that if the high temperature environment in Example 6 is used, the slurry temperature will rise during the high-speed stirring process, the solvent will evaporate faster, and the polymer will be difficult to fully disperse, so that the first stirring cannot achieve the expected dispersion effect, and finally the particle size in Example 6 increases to 10-30 μm after standing for 4 hours. The average power density of the constituent single cells is significantly lower than that in Example 1, and the standard deviation is as high as 0.019, indicating that the slurry is unevenly distributed everywhere; the present invention preferably controls the temperature of high-speed stirring at 10-22°C, which is more conducive to the first stirring dispersion, and significantly improves the stability and uniformity of the slurry;

[0141] (4) Based on Examples 1, 7 and 8, it can be seen that the preferred vacuum drying temperature of the present invention is set at 55-65°C. When the temperature is lowered to 55°C, the drying time is prolonged, resulting in an increase in particle size. When the temperature is raised to greater than 65°C, the drying time remains the same but the effect cannot be effectively improved, and the production energy consumption increases.

[0142] (5) Based on the three groups of comparative data in Examples 1, 4, 5 and Comparative Examples 1 to 3, it can be seen that the two-step preparation process provided by the present invention has obvious advantages in ensuring the stability and uniformity of the slurry;

[0143] (6) Based on Example 1 and Comparative Example 4, it can be seen that water is added during the first mixing in Comparative Example 4, which changes the solvent composition in the slurry system and the solubility of the ionic polymer in the solution, resulting in unsatisfactory dispersion of the slurry and the ionic polymer after the first stirring. After the subsequent vacuum drying, the ionic polymer and the catalyst cannot achieve the effect of locking the spatial structure, which ultimately leads to a significant decrease in the stability and uniformity of the slurry configured in the later stage;

[0144] (7) Based on Example 1 and Comparative Example 5, it can be seen that in Comparative Example 5, vacuum drying is changed to freeze drying, and the drying time is increased from the previous 30-60 min to 24 h. The slurry partially settles and agglomerates during the slow drying process, the ratio of the catalyst to the slurry is not fixed, the particle size of the re-configured slurry is larger, and the stability and uniformity of the slurry are reduced;

[0145] (8) Based on Example 1 and Comparative Example 6, it can be seen that only high-speed stirring without ball milling is used, and the solid phase cannot be evenly dispersed in Comparative Example 6, and the catalyst slurry may agglomerate, resulting in the particle size and slurry uniformity in the slurry failing to meet the requirements.

[0146] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an electrode catalyst slurry suitable for industrial mass production, characterized in that: The preparation method comprises the following steps: (1) mixing a solution of a catalyst and an ion polymer and performing a first stirring, wherein no additional water is added during the first stirring, to obtain a mixed material; wherein the mass ratio of the ion polymer to the carbon in the catalyst is 0.6 to 1.5:1; The first stirring includes ultrasonic oscillation stirring and high-speed stirring performed sequentially; The high-speed stirring temperature is 10 to 25°C; The solid content of the ionic polymer solution is 20% to 30%; (2) The mixed material is vacuum dried at a temperature of 55 to 65° C. to obtain a catalyst-ion polymer solid body; the vacuum drying locks the spatial structure of the ion polymer and the catalyst and forms a catalyst-ion polymer solid body without the need for filtering and washing steps; (3) The catalyst-ion polymer solid body is crushed, and the crushed material, organic solvent and water are mixed, and then subjected to a second stirring and ball milling in sequence to obtain an electrode catalyst slurry; the crushing in step (3) includes grinding; The particle size of the catalyst is 1 to 10 μm, and the particle size of the material after ball milling is 1 to 10 μm.

2. The preparation method according to claim 1, characterized in that: The mixing in step (1) includes: firstly adding a catalyst into a container, then introducing argon gas to expel the air, and then adding the ion polymer solution.

3. The preparation method according to claim 1, characterized in that: The ultrasonic shaking stirring time is 10 to 25 minutes.

4. The preparation method according to claim 1, characterized in that: The frequency of the ultrasonic oscillation stirring is 20-30HKz.

5. The preparation method according to claim 1, characterized in that: The stirring speed of the high-speed stirring is 10000-30000 r / min.

6. The preparation method according to claim 1, characterized in that: The high-speed stirring time is 10 to 40 minutes.

7. The preparation method according to claim 1, characterized in that: The gas after evacuation in step (2) is drawn out from the vacuum drying oven, condensed, and then passed through a vacuum pump.

8. The preparation method according to claim 1, characterized in that: The absolute vacuum degree of the vacuum drying is less than 133 Pa.

9. The preparation method according to claim 1, characterized in that: The particle size of the crushed material is 8 to 15 μm.

10. The preparation method according to claim 1, characterized in that: The stirring speed of the second stirring in step (3) is 10000-20000 r / min.

11. The preparation method according to claim 1, characterized in that: The second stirring time is 5 to 15 minutes.

12. An electrode catalyst slurry, characterized in that: The electrode catalyst slurry is prepared according to the method for preparing the electrode catalyst slurry according to any one of claims 1 to 11.

13. A catalyst coating membrane, characterized in that: It comprises a cathode catalyst layer, an anode catalyst layer and a proton exchange membrane, wherein the anode catalyst layer and the cathode catalyst layer are arranged on both sides of the proton exchange membrane, and the anode catalyst layer and / or the cathode catalyst layer are made of the electrode catalyst slurry as claimed in claim 12.

14. A fuel cell, characterized in that: The fuel cell comprises the catalyst coated membrane of claim 13.

Citation Information

Patent Citations

  • Preparation method for anti-settling fuel cell catalyst slurry

    CN111135761A

  • Preparation method of catalyst slurry for fuel cell and preparation method of membrane electrode

    CN114050277A

  • Electrode catalyst slurry, preparation method thereof, catalyst coating film and fuel cell

    CN113921831A

  • Manufacture of solid polyelectrolyte fuel cell electrode

    JP1995022034A